An Investigation of Teaching and Learning Centers of Ivy League Universities in Terms of Their Contribution to Quality Higher Education - Aylin Akınlar; Derya Kavgaoğlu (Istanbul Kültür University, 2024)
Teaching and learning centers play an important role in ensuring access to high-quality education.  The goal of this research is to investigate the teaching and learning centers of Ivy League universities. The research is qualitative, and the document analysis method was preferred. The data obtained from document analysis were subjected to content analysis. Higher education institutions made up the population of the study, and the sample included the web pages of Ivy League University Teaching and Learning Centers, which were chosen using criterion sampling from purposive sampling methods. According to the research findings, Ivy League Teaching and Learning Centers promote quality higher education through active activities in five categories and 26 themes: strengthening academic and administrative staff, supporting students, developing educational programs, and university-community cooperation. These activities are critical for successful outcomes while applying to higher education institutions in Türkiye and other developing nations. Considering the findings of the study, it is thought that these functions, which make Ivy League Universities a powerful actor in the field of education, would be beneficial to be implemented both in Türkiye and around the world. As a matter of fact, teaching and learning centers serve the individual and society as a national social intervention tool where all stakeholders, the curriculum and the educational institution as a learning organization are also developed by taking education beyond the curriculum.